Beyond the Crisis : Revisiting Emerging Europe's Growth Model - Atoyan, Ruben (Washington, D.C. : International Monetary Fund, 2010)
Focusing on the nexus between economic growth and buildup of external vulnerabilities, this paper provides a systematic account of different growth strategies followed in Central and Eastern Europe in 2000-08 and then uses this growth diagnostics to derive implications for the post-crisis recovery. The main findings point to three policy lessons for improving growth sustainability. First, greater reliance on tradable sectors should be the cornerstone of the future growth model. Second, enhancing domestic sources of bank credit funding would contribute to mitigation of external vulnerabilities and make domestic financial system more resilient to global financial shocks. Third, prudential and macroeconomic policies will have to be more proactive in managing capital inflows, including funneling these inflows into investment in the export-oriented industries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet